Urban Sprawl. How Useful Is This Concept? - Gunther Maier; Gerald Franz; Pia Schrock (European Regional Science Association (ERSA), 2006)
This paper discusses the question whether the city of Vienna, Austria, is experiencing urban sprawl. We will critically evaluate the concept of urban sprawl and analyze its relationship to regular forms of urban development. Particular emphasis will be given to quantitative measures of urban change that might be able to identify key factors of urban sprawl. These measures are then applied to empirical data for the city of Vienna, Austria
Keywords: 330